2017
DOI: 10.1093/bja/aex387
|View full text |Cite|
|
Sign up to set email alerts
|

Intraoperative permissive oliguria – how much is too much?

Abstract: Acute kidney injury (AKI) after general surgery is a serious complication. In abdominal surgery the incidence is around 13%, and it is associated with increased postoperative morbidity, length of hospital stay and a 13-fold increase in the relative risk of inhospital or 30-day mortality. 1 2 Oliguria is one of the oldest markers of AKI, and was historically described by Epheseus and Galen in 100-200 AD. 3 4 By consensus, oliguria is defined as urine output <0.5 ml kg À1 h À1. 5 Perioperative causes of oliguria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Several studies have attempted to derive urine output thresholds that identify AKI in surgical patients [30,31,32]. Using a methodology that was similar to ours, one retrospective study in cardiac surgical patients undergoing cardiopulmonary bypass identified a urine flow rate of <1.5 mL/kg/h as a cutoff that was associated with AKI risk [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have attempted to derive urine output thresholds that identify AKI in surgical patients [30,31,32]. Using a methodology that was similar to ours, one retrospective study in cardiac surgical patients undergoing cardiopulmonary bypass identified a urine flow rate of <1.5 mL/kg/h as a cutoff that was associated with AKI risk [30].…”
Section: Discussionmentioning
confidence: 99%
“…Along with the usual <0.5 or <0.3 mL/kg/h cutoff of oliguria, our analysis suggested significant associations between low urine flow rate of <1.0 mL/kg/h and risk of AKI after LDLT. We evaluated the cutoff of oliguria up to 3.0 mL/kg/h because previous studies reported different cutoffs of oliguria during surgery [30,31,32] (Supplemental Table S2). The significant threshold of <1.0 mL/kg/h may be influenced by the intraoperative diuretics use.…”
Section: Discussionmentioning
confidence: 99%
“…5,58 Although traditionally oliguria is taken as a sign of hypovolaemia and subsequent reduction in kidney perfusion, perioperative oliguria now is not always abnormal, especially when no other signs of hypoperfusion are present. 5,59 In a recent study, there was no significant correlation between oliguria and postoperative renal failure, but there was an increase in acute kidney injury associated with increased postoperative fluid balance. 60 Although anuria is abnormal and should be taken seriously, oliguria, however, can be a normal and expected occurrence as a result of judicious fluid management in the perioperative period.…”
Section: Oliguria In the Postoperative Periodmentioning
confidence: 98%
“…No correlation was found for a cut-off between 0.3 and 0.5 mL/kg/h and the development of postoperative AKI [ 16 ]. These findings provide further support for interpreting oliguria within the clinical context in that a relatively reduced urine output albeit greater than 0.3/ml/kg/h is likely to represent a (reversible) physiological response to perioperative stimuli including intravascular hypovolemia, reduced renal perfusion due to hypotension and release of anti-diuretic hormone in response to nausea or pain [ 31 ]. Ralib et al were able to confirm by analyzing 725 admissions to a general ICU, that a urine output threshold of 0.5 ml/kg/h may be too liberal given that a threshold for 6-h UO of 0.3 ml/kg/h was best associated with the combined endpoint of dialysis or mortality.…”
Section: Urine Output Thresholdmentioning
confidence: 90%